Te Mata Ira—Faces of the Gene: Developing a cultural foundation for biobanking and genomic research involving Māori. (December 2016) - Hudson, Maui; Russell, Khyla; Uerata, Lynley; Milne, Moe; Wilcox, Phillip; Port, Ramari Viola; Smith, Barry; Toki, Valmaine; Beaton, Angela
Te Mata Ira was a three-year research project (2012–2015) that explored Māori views on genomic research and biobanking for the development of culturally appropriate guidelines. A key component of this process has been to identify Māori concepts that provide cultural reference points for engaging with biobanking and genomic research. These cultural cues provide the basis for describing the cultural logic that underpins engagement in this context in a culturally acceptable manner. This paper outlines the role of two wānanga (workshops) conducted as part of the larger project that were used to make sense of the Māori concepts that emerged from other data-collection activities. The wānanga involved six experts who worked with the research team to make sense of the Māori concepts. The wānanga process created the logic behind the cultural foundation for biobanking and genomic research, providing a basis for understanding Māori concepts, Māori ethical principles and their application to biobanking and genomic research.